2012
DOI: 10.1002/mnfr.201100683
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene inhibits angiogenesis both in vitro and in vivo by inhibiting MMP‐2/uPA system through VEGFR2‐mediated PI3KAkt and ERK/p38 signaling pathways

Abstract: Our data demonstrate the anti-angiogenic effect of lycopene both in vitro and in vivo. The anti-angiogenic activity of lycopene may involve inhibition of MMP-2/uPA system through VEGFR2-mediated PI3K-Akt and ERK/p38 signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…Furthermore, AXIIR siRNA was able to increase the expression of tissue inhibitor of metalloproteinase 2 (TIMP2), which was regularly accompanied with the suppression of MMP2 and MMP9 (Fig. 5C) [15]. Many studies had indicated that ERK1/2 and AKT were involved in activities of MMP2 and MMP9 [16,17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, AXIIR siRNA was able to increase the expression of tissue inhibitor of metalloproteinase 2 (TIMP2), which was regularly accompanied with the suppression of MMP2 and MMP9 (Fig. 5C) [15]. Many studies had indicated that ERK1/2 and AKT were involved in activities of MMP2 and MMP9 [16,17,18].…”
Section: Resultsmentioning
confidence: 99%
“…The induction of cell differentiation (52) via the restoration of gap junctions (57) has also been suggested. Other mechanisms include prevention of oxidative damage (58,59) , inhibition of angiogenesis (59,60) , induction of phase II enzymes (61)(62)(63) , interaction with growth factors and sex hormones (64) and the induction of nuclear receptors activation (65)(66)(67) . Lycopene has also been found to confer photoprotection (68) .…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Urokinase-type plasminogen activator (uPA) binding to urokinae plasminogen activator receptor can activate the conversion of plasminogen to plasmin [22,23]. Therefore, the inhibition of VEGFR2 and MMPs/uPA system is regarded as a therapeutic strategy against angiogenesis [22,23]. However, effects of 2-DG on these molecules are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Pro-MMPs can be converted into a matured form of MMPs by plasmin, which is derived from plasminogen [21]. Urokinase-type plasminogen activator (uPA) binding to urokinae plasminogen activator receptor can activate the conversion of plasminogen to plasmin [22,23]. Therefore, the inhibition of VEGFR2 and MMPs/uPA system is regarded as a therapeutic strategy against angiogenesis [22,23].…”
Section: Introductionmentioning
confidence: 99%